(untitled) (Research, Society and Development, 2021)
The Amazon is the largest tropical forest in the world and is home to around 20% of all the biodiversity on the planet, among the species present in the Amazon is Copaifera langsdorffii, exploited mainly for the extraction of oil-resin and wood, often in ways incorrect, which can cause the loss of genetic variability. The aim of this study was to evaluate the genetic structure and diversity among individuals of C. langsdorffii located in Mato Grosso, Brazil, using ISSR markers. We sampled leaves from 27 adult individuals of C. langsdorffii, whose total genomic DNA was extracted. A total of 12 ISSR primers were used for the molecular characterization of the individuals. A grouping analysis was performed using the unweighted pair group method, Bayesian analysis and characterized by the genetic diversity. The genetic diversity among and within the groups was demonstrated by the AMOVA. As a result, 106 fragments were amplified and 98.11% were polymorphic. The polymorphic information content of each primer ranged from 0.45 to 0.81. The dendrogram showed the formation of 4 distinct groups. The greatest genetic variability is found within the groups and not between them. The percentage of polymorphism, genetic dissimilarity values and genetic diversity indexes indicate that there is high genetic variability among Copaifera langsdorffii individuals, suggesting that ISSR primers were efficient in detecting polymorphism in this species and that the individuals have potential for compose programs aimed at the preservation of the species and the ability to integrate germplasm banks.